Prognostic implications of nonsustained ventricular tachycardia morphology in high‐risk patients with hypertrophic cardiomyopathy. (9th June 2020) - Adduci, Carmen; Boldini, Francesca; Palano, Francesca; Musumeci, Beatrice; De Lucia, Carmine; Russo, Domitilla; Volpe, Massimo; Autore, Camillo; Francia, Pietro
Abstract: Introduction: The prognostic impact of nonsustained ventricular tachycardia (NSVT) morphology has never been explored in hypertrophic cardiomyopathy (HCM). In a single‐center cohort of consecutive HCM patients implanted with an implanted cardioverter‐defibrillator (ICD), we assessed NSVT morphology patterns and their prognostic implications. Methods: A cohort of consecutive HCM patients implanted with an ICD was followed from ICD implantation to last follow‐up visit. Patients were assessed for NSVT as stored events in ICD memory. Ventricular tachycardias (VTs) were classified as monomorphic (MM) or polymorphic according to intracardiac electrogram morphology. Results: One hundred nine consecutive HCM patients (68 males; mean age: 45 ± 17 years) composed the study population. During follow‐up (71 ± 48 months), 7 polymorphic NSVT in 4 patients and 370 MM NSVT in 42 patients were retrieved from ICD memory. Among patients with only MM NSVT, 19 (45%) had one morphology, 17 (41%) had two morphologies, 3 (7%) had three morphologies, and 3 (7%) had four morphologies. Patients with polymorphic NSVT had the highest risk of ICD interventions (HR, 5.04; 95% CI, 1.26‐20.19; P = .02). A stepwise increase of the risk of ICD interventions in patients with two, three, and four NSVT morphologies was observed. Out of 16 patients with both NSVT and ICD‐treated VTs, 13 (81%) had at least one ICD‐treated VT with the same morphology of a previous long‐lasting NSVT. Conclusions: In high‐risk HCM patients, the occurrence of polymorphic NSVT and of NSVT with multiple morphologies carries a high risk for ICD interventions. Sustained VTs tend to recur with the same morphology of previous long‐lasting NSVTs.